Oestrogens in milk and breast cancer: a cause for concern…or not?. Issue 2 (May 2020) - Peaker, Malcolm
Abstract: In this short Research Reflection I address and refute the suggestion that oestrogens consumed in milk might contribute in a significant way to endogenous levels and thereby have a physiological action, possibly resulting in adverse consequences including increased breast cancer risk. Quantitative analysis based on published data shows that, even in worst case scenarios, oestrogen consumption in milk is considerably less than regulatory bodies regard as entirely safe.